DETERMINAN MINAT PENGGUNAAN SOCIAL COMMERCE: PENDEKATAN THEORY OF REASONED ACTION - Siwi Nurjayanti SE (Jurnal Ilmiah Mahasiswa FEB, 2019)
The purpose of this research is to predict and identify the determinant of the intention to use social commerce. The construct of this research comprised of attitude, subjective norms, price value, social support, social commerce construct (SCC) and intention to use. Moreover, this research is a development of the Theory Reasoned Action model from the previous studies and also the survey method was used to collect the data and the questionnaire method as the instrument of this research. The sample of this research are the bachelor students of faculty of economics and business of Brawijaya University that have the intention to use and already using social commerce on their online shopping activities. There were 80 samples collected from the questionnaire that were able to used in this research. The results of this research show that price value, attitude, SCC and subjective norms influencing the intention to use social commerce and the price value is proven to be the main factor because it has the biggest influence. However, the result of this research also show that social support has no influence on the intention to use social commerce. Keywords : social commerce, price value, attitude, social commerce construct, subjective norms, behavioral intention, theory of reasoned action